Recent Trends in CAPTCHA Security and Bot Challenges - Singh, Shivank; Chawda, Rahul kumar (International Journal of Computer Sciences and Engineering, 2020)
CAPTCHA is a security mechanism which is basically used to distinguish between human and bots in automated online systems. Here bot means software robots that are used for brute force attacks or webmail bombarding or DOS attack to the system. CAPTCHA is also useful for protected web services from various types of dynamic attacks every day. Generally, it is seen in online registration form for preventing spam applications. In this paper, we have studied the various types of CAPTCHA like picture CAPTCHA, video CAPTCHA, content CAPTCHA, sound CAPTCHA and their uses in present environments.